Immunoglobulin classes of DNA binding activity in serum and skin in systemic lupus erythematosus. - Pennebaker, J B (1977)
36 systemic lupus erythematosus patients with native DNA binding activity (nDNA-BA) in the serum and subepidermal immunoglobulin deposits were studied to determine the relationship of the immunoglobulin (Ig) class distribution of serum nDNA-BA to the clinical characteristics of their disease and to the Ig class present at the dermal-epidermal junction (DEJ). The patients with predominantly (86-98%) IgM nDNA-BA in the serum had less active disease, mild or no renal involvement, and longer survival than those with predominantly (51-95%) IgG nDNA-BA in the serum. Renal biopsies in eight patients with predominantly IgM nDNA-BA in the serum showed relatively benign histologic changes in the kidney. In contrast, renal tissue from 23 patients with predominantly IgG nDNA-BA showed more severe histologic changes. All patients had multiple skin biopsies. Patients with predominantly IgM nDNA-BA consistently had only IgM at the DEJ. Patients with predominantly IgG nDNA-BA had IgG, usually in association with IgM, at the DEJ. The findings demonstrate that a minority of systemic lupus erythematosus patients may exhibit a limited anti-nDNA response characterized by the presence of chiefly IgM nDNA-BA in the serum and that this is reflected by the presence of mild disease and IgM alone at the DEJ. The development of IgG nDNA-BA is associated with more severe and active disease.